INFORMATION SECURITY AWARENESS MODEL FOR EMPLOYEES IN BANK ALBILAD - al-Haddad, Abdulqadeer Sheikh Aidaros, 1990-, author; Nurazean Maarop, Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Jaminan Maklumat))-Universiti Teknologi Malaysia, 2015